P295 Comparative Assessment of Infliximab Trough Levels between Point-of-Care Testing and current Standard of Care (enzyme linked immunosorbent assay) in patients with Inflammatory Bowel Disease. (27th May 2021) - Maniero, D; Lorenzon, G; Marsilio, I; Rigo, A; Cardin, R; Facchin, S; Barberio, B; D'Incà, R; Zingone, F; Bahur, B; Bray, K R; Savarino, E V
Abstract: Background: Infliximab (IFX) is a monoclonal antibody that targets cytokine tumor necrosis factor; it is used for the treatment of patients with active inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC). IFX induces and maintains remission and mucosal healing in patients with IBD. Measurement of trough levels (TL) of IFX is important to assess if the drug is within its therapeutic concentrationand to explain lack/loss of response. Standard laboratory tests to assess IFX trough levels (enzyme linked immunosorbent assays, ELISA) present some downsides, related to the long turnaround (about 3 hours), and the need of specialized equipment and laboratory personnel. For this reason, point-of care testing (POCT) was developed to provide results within a few minutes from blood collection, leading to a decision-making approach. Aim: To determine the degree of analytical correlation between a recently developed POCT (ProciseDx) IFX assay which analyze capillary whole blood and the comparative ELISA from serum. Methods: From October 2020 to January 2021, patients (aged≥18 years) taking IFX were recruited at Gastroenterology Unit, Padua University Hospital. In each patient, IFX levels from capillary whole blood collected by finger stick were performed using the ProciseDx IFX assay with reportable range between 1.7-77.2 µg/mL; at the same time, a serum sample from venous blood was collected to carry out Grifols' Promonitor ELISA test (range 0.035–14.4 µg/mL). A Deming regression test was used to identify the correlation between the two methods. Results: Eighty-seven patients were enrolled (63% males; mean age of 44±16), with 52% of them having CD, 45% UC and 3% an undetermined-Inflammatory Bowel Disease. The assessment with ProciseDx POCT was feasible in each patient and only in three cases blood collection from finger prick was repeated. Moreover, from blood collection to results we needed about 3±0.5 minutes, while serum ELISA analysis required the collection of at least 40 samples (around three weeks at our centre) and 3 hours to be performed. 39 patients (59% males; mean age of 44±16) had TL as assessed by ProciseDx IFX assay lower than 1.7 or greater than 14.4 µg/mL, in accordance with ELISA assessment. Among the remaining 48 patients (67% males with mean age of 45±17), The correlation between the two tests was high (the total results showed an R squared of 0.691 (95% CI 0.717-0.902). Conclusion: The ProciseDx POCT has good accuracy but was more rapid and easy to be performed in providing the results of Therapeutic Drug Monitoring in outpatients taking IFX. This could lead to a more effective optimization of the biological drug, thus avoiding treatment failure.